Overview of the Challenges Affecting the Accountability of the Municipal Manager in Mahikeng Local Municipality - Chitimira, Howard; Sethunyane, Tumelo; Magau, Phemelo (Acta Universitatis Danubius. Juridica, 2023)
Accountability is one of the important principles and values for the proper and effective management of municipalities in the local government in South Africa. This article provides an overview of the challenges affecting the accountability of the municipal manager in Mahikeng local municipality. The article identifies the failure to account, the failure to comply with the legislative framework for accountability, the lack of compliance with the ethical standards, the municipality having too many creditors, the failure to follow proper communication channels as some of the challenges affecting the accountability of the municipal manager in the Mahikeng local municipality. These challenges have affected the effective service delivery in the Mahikeng local municipality. To this end, the authors argue for enhancing the enforcement approaches and compliance with the relevant laws and prescripts in order to curb the irregular, unauthorised, wasteful and fruitless expenditure in the Mahikeng local municipality.